Influence of halal awareness, certification, marketing and knowledge on non-muslim consumers’intention to purchase halal products in Malaysia - Rajandran, Thurga (2025)
This study investigates significant influence of halal awareness, certification, marketing and knowledge on Non-Muslim consumers’ intention to purchase halal products in Malaysia. These findings underscore importance of increasing awareness, ensuring transparent certification, and leveraging effective marketing strategies to attract non-Muslim consumers. This study is to support plans for engaging a diversified consumer base in growing global halal market and help Malaysia maintain its leading position in halal economy by addressing these factors. Employing a quantitative approach, data were collected through an anonymous questionnaire distributed to 182 non-Muslim respondents using intercept surveys. Stratified sampling has been used in this study. Statistical technique ensures representative samples are obtained from different subgroups or strata within a population, was employed to improve data reliability. The questionnaire explored four key factors which is halal awareness, certification, marketing, and knowledge and using a structured format and Likert scale for measurement. The data were analyzed using SPSS 29, applying descriptive statistics, regression, and Pearson's correlation analyses. Results revealed significant relationships between non-Muslim consumers' purchase intentions and halal awareness (β=0.172, p=0.010), certification (β=0.474, p<0.001), marketing (β=0.271, p=0.006), and knowledge (β=0.136, p=0.048). This study offers recommendations to Ministry of Higher Education (MOHE), halal certification bodies, and industry players. MOHE is encouraged to integrate halal-related topics into academic curricula to prepare graduates for growing halal market. Certification bodies should establish standardized global criteria to build trust and reduce consumer confusion. Industry players are urged to promote halal certification prominently in product development and marketing to enhance consumer confidence and broaden market appeal